Acute consumption of a caffeinated energy drink enhances aspects of performance in sprint swimmers - Lara, B.; Ruiz-Vicente, D.; Areces, F.; Abian-Vicen, J.; Jose Salinero, J.; Gonzalez-Millan, C.; Gallo-Salazar, C.; Del Coso, J. (British Journal of Nutrition, 2015)
This study investigated the effect of a caffeinated energy drink on various aspects of performance in sprint swimmers. In a randomised and counterbalanced order, fourteen male sprint swimmers performed two acute experimental trials after the ingestion of a caffeinated energy drink (3 mg/kg) or after the ingestion of the same energy drink without caffeine (0 mg/kg; placebo). After 60 min of ingestion of the beverages, the swimmers performed a countermovement jump, a maximal handgrip test, a 50 m simulated competition and a 45 s swim at maximal intensity in a swim ergometer. A blood sample was withdrawn 1 min after the completion of the ergometer test. In comparison with the placebo drink, the intake of the caffeinated energy drink increased the height in the countermovement jump (49·4 (sd 5·3) v. 50·9 (sd 5·2) cm, respectively; P0·05). A caffeinated energy drink increased some aspects of swimming performance in competitive sprinters, whereas the side effects derived from the intake of this beverage were marginal at this dosage.